Immunohistological features of the collagen formation in ovaries of fetuses from mothers with a physiological pregnancy on different gestational terms - Kupriianova, L.; Ivanchenko, S. (Journal of Education, Health and Sport, 2022)
The comprehensive study on the fetal ovaries allowed us to disclose main features of the collagen synthesis in different organ’s components relatively to the gestational term of fetus. We have studied the ovaries’ structure in case of fetuses, who died both antenatally and intranatally. The mothers of fetuses, according to the medical documentation, were healthy. As a reason of the fetuses death we can name an acute violation of the utero-placental as well as placental-fetal circulation. According to the specific features of the organs’ development, all fetuses were divided into groups: 21-28 weeks, 29-36 weeks, 37-40 weeks. The research methods: macroscopic, morphometric, histological, immunohistochemical, statistical. We have described a histological structure of the ovaries as well as we have postulated, that this structure corresponds completely with the physiological norm in every term of gestation. By applying the immunohistochemical method we have postulated, that the collagen of the I type prevails in the collagen structure of the connective tissue of fetal organs. It is manifested as an intensive glow. As the same time, the collagen of the III type is manifested as the small foci of moderate intensity. There are two types of collagens in the walls of blood vessels: IV and III ones. Moreover, we can preferably notice the collagen of the IV type. The collagen of the III type, at the same time, is manifested by foci with a low intensity of glow. All specific features of the collagen formation in the structure of the connective tissue, that were described above, are the same with ones which are corresponding with the physiological norm. The histological and immunohistochemical features of the ovaries’ structure, in case of fetuses from the study groups, could be applied as a comparison in a study on the organs’ structure in case of fetuses from mothers with a complicated pregnancy.